Bizarre Waveforms in Strong Motion Records - Baofeng Zhou; Haiyun Wang; Lili Xie; Yanru Wang (Shock and Vibration)
This paper collects a rich set of strong motion records in some typical earthquakes domestic and abroad, checks its seismic events, converts the data format, corrects the zeroline and draws the waveform. Four kinds of abnormal phenomena on the acceleration waveform are revealed, such as spike, asymmetric waveform, obvious baseline drift, and strong motion records packets separation. Then reasonable processing approaches are derived from the preliminary analysis of the generation mechanism for abnormal phenomena. In addition to the effects on time history, Fourier amplitude spectrum and response spectrum are studied before and after strong motion records correction. It is shown that (1) mechanism of spikes is rather complicated; however spikes can be eliminated by “jerk” method, ratio method, and the consistency of the three-component PGA time; (2) mechanism of the asymmetric waveform is of diversity; however, to some extent, the Butterworth low-pass filtering can be applied to correct it; (3) two pieces of strong motion record packets can be connected by searching continuous and repeated data; (4) the method of cumulative adding can be used to find the clear baseline drift; (5) the abnormal waveform directly affects the characteristics of time history and frequency spectrum.